2007
DOI: 10.1210/en.2007-1257
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A Inhibits Glucagon Secretion and Gene Expression through a Foxo1-Dependent Pathway

Abstract: Orexin-A (OXA) regulates food intake and energy homeostasis. It increases insulin secretion in vivo and in vitro, although controversial effects of OXA on plasma glucagon are reported. We characterized the effects of OXA on glucagon secretion and identify intracellular target molecules in glucagon-producing cells. Glucagon secretion from in situ perfused rat pancreas, isolated rat pancreatic islets, and clonal pancreatic A-cells (InR1-G9) were measured by RIA. The expression of orexin receptor 1 (OXR1) was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 35 publications
(32 reference statements)
4
38
0
Order By: Relevance
“…7. Previous studies have demonstrated that OXR1 is clearly expressed in pancreatic islets and beta cells of pigs, rats and mice [9][10][11]. Here, we showed that OXA influenced insulin secretion in pancreatic islets through OXR1, but not OXR2.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…7. Previous studies have demonstrated that OXR1 is clearly expressed in pancreatic islets and beta cells of pigs, rats and mice [9][10][11]. Here, we showed that OXA influenced insulin secretion in pancreatic islets through OXR1, but not OXR2.…”
Section: Discussionsupporting
confidence: 47%
“…In the fasting state, OXA potently inhibits glucagon secretion in perfused rat pancreas [11] and rats in vivo [14]. Consistently, OXA decreases blood glucose levels in fasting mice [15].…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations